FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN PENINGKATAN NILAI AMBANG DENGAR PADA PEKERJA DI BAGIAN PRODUKSI BODY MINI BUS PT. X MAGELANG - Indriani Putri Kusumadewi; Ari Suwondo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Noises that exceeded the threshold value in production process could lead to work-related disease which is the increasing in hearing threshold value for factory workers. A research showed that noises sources were coming from the production process and the machineries such as las blender and las plasma. This research aimed to find out risk factor that related with the increasing of hearing threshold of Body Mini Bus Production workers in PT. X Magelang. This research was an observational analitic study with a cross sectional study approach. The population from this research were 138 workers. The sample of this research was chosen from simple random sampling from 57 workers. The measurements done by the researcher to the workers were based on blood pressure with Sphygmomanometer, blood glucose levels with Nesco Multicheck, hearing threshold value with an audiometer, and interviews with questionaire. The results showed that noise intensity for individual worker in point 1 was 94 dB while individual worker in point 2 was 93 dB. According to analysist 91.2% of workers were categorized as of hearing threshold value were interrupted while Chi Square and Odd Ratio test resulted that noise intensty related with the hearing threshold value (sig = 0.011), working period related with increasing of hearing threshold value (sig = 0.006), and age related with the hearing threshold value (sig = 0.045). Cintructive input to PT. X was to give working rotation regularly, support protection for deaf caused working environment programs, and safety working equipment improvement. For workers it was highly recommended to wear earplug while working.